2014
DOI: 10.3109/0142159x.2014.956055
|View full text |Cite
|
Sign up to set email alerts
|

Procedure-based assessments in trauma and orthopaedic training – The trainees’ perspective

Abstract: This is the first nationwide study offering a deeper insight into factors influencing T&O trainees' perceptions of the educational benefit gained from using PBAs. This study informs the debate on how to improve the effective use of PBAs in T&O training, and generally, of workplace-based assessments in surgical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 15 publications
1
48
0
1
Order By: Relevance
“…For example, one study on MSF reported that 89% of trainees agreed the comments were useful, whereas 38% agreed the numeric report was useful . Trainees particularly valued the verbal delivery of performance information . In a study conducted by Sabey and Harris, 94% of trainees described their verbal feedback as useful compared with 74% for written comments .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, one study on MSF reported that 89% of trainees agreed the comments were useful, whereas 38% agreed the numeric report was useful . Trainees particularly valued the verbal delivery of performance information . In a study conducted by Sabey and Harris, 94% of trainees described their verbal feedback as useful compared with 74% for written comments .…”
Section: Resultsmentioning
confidence: 99%
“…These perspectives led to a view of such assessments as ‘form‐filling’ or ‘tick‐box’ initiatives:
Now it is just so people can tick the boxes. The inspiration and pride in our profession has gone.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations